2022
DOI: 10.3389/fimmu.2022.990224
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the efficacy and safety of cryoablation and intra-arterial PD-1 inhibitor in patients with advanced disease not responding to checkpoint inhibitors: An exploratory study

Abstract: ObjectiveTo explore the effectiveness of cryoablation combined with arterial perfusion with programmed cell death protein 1 inhibitors in overcoming immune resistance in advanced solid cancers.MethodsIn this pilot retrospective study, nine patients with solid cancers were treated with tumour cryoablation and arterial perfusion with programmed cell death protein 1 inhibitors, which had previously proven ineffective. The CIBERSORT software was used to estimate the levels of tumour-infiltrating immune cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…An additional promising advantage of cryoablation is that it may favour a specific immune response against tumours, which may stimulate or enhance the combined efficacy of antitumour immunotherapy. [27][28][29][30][31] Compared with the percutaneous approach, the transbronchial approach seems to be a promising therapeutic alternative with a lower risk of pneumothorax. 9 32 Previous studies have reported that transbronchial RFA and MWA are feasible for the treatment of early-stage peripheral lung cancer.…”
Section: 10mentioning
confidence: 99%
“…An additional promising advantage of cryoablation is that it may favour a specific immune response against tumours, which may stimulate or enhance the combined efficacy of antitumour immunotherapy. [27][28][29][30][31] Compared with the percutaneous approach, the transbronchial approach seems to be a promising therapeutic alternative with a lower risk of pneumothorax. 9 32 Previous studies have reported that transbronchial RFA and MWA are feasible for the treatment of early-stage peripheral lung cancer.…”
Section: 10mentioning
confidence: 99%